MANAJEMEN SDM BERBASIS INTEGRITAS DAN DAMPAK: STRATEGI PENGEMBANGAN TENAGA PENDIDIK UNTUK PENDIDIKAN INDONESIA MAJU - Rahmawati, Milatul; Kurnia, Mahyori; Nellitawati, Nellitawati; Kadri, Hanif Al; Setiawati, Merika (Jurnal Manajemen Pendidikan, 2025)
Improvements in the quality of education in Indonesia are highly dependent on the competence and character of educators as the spearhead of learning system transformation. This article examines the concept and implementation of human resource management (HRM) in the education sector using an integrity-based and impact-based approach. By highlighting issues such as low professional integrity, competency gaps, and weak outcome-based evaluation systems, this paper proposes HR development strategies that are not only focused on administrative performance but also on tangible contributions to the transformation of students and society. This approach includes values-based recruitment, transformational training, and performance evaluation based on social change. Case studies from the Guru Penggerak program and lessons learned from international practices demonstrate that educators managed with principles of integrity and impact orientation can create an ethical, transformative, and sustainable learning environment. This article recommends reforms in education HR management policies to achieve an advanced and globally competitive Indonesian education system.